The Effect of Redenomination of Iraqi Currency on the General Level of Prices - Mustafa Khadum Najaf Abadi, Jawad kadhim Al-Bakri, Husham Sabeeh Zaier Maqsoosee (International Journal of Advanced Science and Technology, 2020)
The reformation of currency management system is significant and achieved by redenominating or eliminating zeros from it in order to control its value. The probability of redenomination has created controversy in monetary, economic and public media. The objective of the study is to clarify the effect of three zeros elimination from Iraqi dinar as well as to measure the probable cost and the benefit it might bring to Iraqi economy. The reason of redenomination is an attempt to reduce the negative impact from Iraqi currency resulted from high denomination banknote with lower value. The paper consists of four sections. The first is an introduction about the significance of redenomination from the currency. The second section is literature review concerning previous studies and finally the research ends up with discussion and conclusion. The study hypothesizes that the redenomination from the currency contributes to reduce the inflation of restore the trust in Iraqi dinar as a reserve and to stimulate the economy.